Standarized Basics in Depicting Walis in the Early Age of Islam (Journal of the College of Education for Women, 2019)
Despite the simplicity that characterized the administration in the era of the Prophet(peace be upon him), but it put the Muslim community nucleus Administrative Organizationwho walked Garret Caliphs (RIP) and came after them, who added to this organization whatthey found necessary and dictated by their conditions of life has begun regulation Managingthis appoint leaders and armies of workers on the state and various tribes to spread the Islamicreligion and to teach people the provisions of the Koran and Altfvh in religion and establishprayer and collect Zakat money so you do not appoint leaders and workers and governorsfollowed random, but it is in an objective manner takes reasons to meet expectations.